2019
DOI: 10.1080/21632324.2018.1560926
|View full text |Cite
|
Sign up to set email alerts
|

International remittances and household food security in Sub-Saharan Africa

Abstract: The impact of international remittances on various social, economic and political phenomena has been studied by scholars. A limited number of these studies have examined whether international remittances influence household food security. However, most of these studies are country-specific. Other studies explore specific regions or towns within a country. Cross-country studies on the topic are lacking. We attempt to fill this gap by examining data for over 48,000 people in 32 Sub-Saharan African countries. Our… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 42 publications
6
35
0
Order By: Relevance
“…This is consistent with a broader neglect of the connections between international and internal migration and food security [26][27][28]. More recently, several studies have demonstrated that there is a positive macro-level relationship between food security and the volume of remittances received [29][30][31][32].…”
Section: Introductionsupporting
confidence: 73%
“…This is consistent with a broader neglect of the connections between international and internal migration and food security [26][27][28]. More recently, several studies have demonstrated that there is a positive macro-level relationship between food security and the volume of remittances received [29][30][31][32].…”
Section: Introductionsupporting
confidence: 73%
“…Since remittances are associated with welfare of households, particularly for those whose head is male or lower educated (Murakami et al, 2020). Studies have shown that remittances improve household welfare (Adams, 2011;Andersson, 2012;Ivlevs et al, 2017;Sulemana et al, 2018). Since remittances augment household incomes and thereby improve livelihoods, remittances influence many social, economic, and political phenomena in the migrant's home country (Chauvet & Mercier, 2014;Ivlevs & King, 2017;Levitt, 1998;Nikolova et al, 2017).…”
Section: Significant Decline In Remittances To Severely Impact Households In the Time Of Covid-19mentioning
confidence: 99%
“…In Africa, it is one of the most important sources of external resources in many African countries that has real impacts on lives of millions of recipient families across Africa (African Union, 2016). Although remittance flows to Africa are relatively smaller compared to many other developing regions, their contributions to economic growth are enormous and thereby influence quality of life or wellbeing of relatives left behind (Fayissa & Nsiah, 2010;Pradhan et al, 2008;Sulemana et al, 2018). In addition, remittances have contributed to the alleviation of poverty (Masron & Subramaniam, 2018), to access to water, food, medicine, housing, and clean energy (Ebadi et al, 2018;Ndiaye et al, 2016;UN, 2019), to promoting entrepreneurship (UNDP, 2016), and to empowering women (Sambo, 2016).…”
Section: The Impacts Of Remittance On the African Economy (The Nexus Between Remittance And Economic Growth)mentioning
confidence: 99%
“…One study of 109 developing countries found that “remittances are positively associated with bank deposits and credit,” crucial safeguards against destitution in the face of unexpected environmental and economic shocks (Aggarwal, Demirgüç‐Kunt, & Pería, 2011, p. 262; see also IFAD, 2017). A recent study of 32 sub‐Saharan African countries shows a positive association between household remittance receipts and food security (Sulemana, Anarfo, & Quartey, 2019).…”
Section: Remittancesmentioning
confidence: 99%